Contributions to mathematical pharmacology: new receptor theory with dimeric receptor models - CARLA WHITE (2021)
Classical receptor theory is largely built on assumptions of monomeric receptors. In this thesis, we contribute to receptor theory by considering the now widely accepted cases of dimeric receptors. The implications of dimerisation for drug discovery and therapeutics remain unclear. Therefore, a theoretical consideration of ligand binding and signalling via receptor dimers is warranted. Here, we develop mathematical models for ligand bind-ing at dimerised and dimerising receptors. A key factor in developing these theoretical models is cooperativity across the dimer, whereby binding of a ligand to one protomer aﬀects the binding of a ligand to the other protomer. The eﬀects of cooperativity on binding dynamics are a primary point of interest.The ﬁrst models we present focus on G protein-coupled receptors, where we assume that all receptors are pre-dimerised. Ligand binding models give linear systems of diﬀer-ential equations which we use to analyse time course behaviours. At equilibrium, these models may exhibit multi-phasic log dose response curves, critically depending on co-operativity factors. When considering receptor activation, we see dose response curves that are indicative of non-standard ligand-receptor interactions, giving a quantitative and qualitative platform for analysing and interpreting data when dimers are suspected. A ligand induced model for vascular endothelial growth factor receptors is developed, whereby receptors exist constitutively as monomers and dimerise in response to ligand binding. The resulting nonlinear system of diﬀerential equations is investigated using numerical computations and perturbation methods. We see an excellent ﬁt to published data, validating the model.The utility of our models in parameter estimation is explored theoretically using structural identiﬁability analysis. This determines which parameters can be theoretically estimated from ﬁtting. This analysis is valuable but often overlooked when ﬁtting to ligand-receptor interaction models. We explore the identiﬁability of some canonical lig-and binding models, and our dimer binding models, providing a tutorial and results to contribute to the receptor theory toolbox.